The Great Recession and Life Satisfaction: The Unique Decline for Americans Approaching Retirement Age - John Ifcher; Homa Zarghamee; Amanda Cabacungan (Institute of Labor Economics (IZA), 2016)
Using data from the U.S. Centers for Disease Control and Prevention's Behavioral Risk Factor Surveillance System, we examine the impact of the Great Recession on subjective well-being (as measured by life satisfaction) and attempt to identify disparate effects by age. We find that those approaching retirement age (aged 55 to 64) experienced reduced life-satisfaction after the recession, whereas younger working-aged adults did not. The disparate effects by age cannot be explained by income or unemployment trends, but may be explained by wealth effects. For example, we find that the life satisfaction of those approaching retirement age, but not of younger working-age adults, is closely correlated with wealth indices (e.g., the Case-Shiller Housing Price Index and the S&P 500 Index).
Keywords: G01; D14; D91; D6; I31; 330; subjective well-being; life satisfaction; Great Recession; wealth effect; retirement; and happiness